Neutrophilic Dermatoses in Autoimmune Diseases: Report of Two Cases Associated with Autoimmune Thyroiditis - Angelo Cassisa (MDPI AG, 2018)
The term "neutrophilic dermatoses" includes a rare inflammatory pattern characterized by neutrophil-rich cutaneous infiltrate. Both innate and adaptive immune pathways may be involved in neutrophil recruitment. Occasionally, neutrophilic dermatoses may occur in association with autoimmune thyroiditis. Pathogenetic aspects of this autoimmune disorder may elucidate their possible connection. Two exemplificative cases are taken as a pretext for a short review of this topic.